Exploring the impacts of the Lesotho Highlands Water Project on the sustainable livelihoods of resettled communities - Liphoto, Mosili Jacqueline (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.